Partum Hominis (2024)
The degree project presents a plastic proposal that is based on reflection on the preservation linked to spaces with abundant vegetation. To do this, a work is proposed that involves the languages of painting, installation and clay, understood as: the tool that man has used since his beginnings in making plastic, giving an account of the world. Developments with an iconographic order are taken into account in different cultural processes related to native groups of America and Europe such as: the mayans and vikings, in which in their plastic evolution a connection with the cosmos and life can be seen. , manifesting it through artistic pieces on different materials and supports such as: stone, clay, wood, among others; these account for some relationships between nature and the immaterial world, at the same time they keep ancestral knowledge from their technique